HISTOLOGICAL STUDIES ON THE ALIMENTARY CANAL OF THE MILLIPEDE, ANOPLODESMUS TANJORICUS (POCOCK), (DIPLOPODA: POLYDESMIDA) - S. V. DESHMUKH; C. K. DESHMUKH (The Bioscan, 2011)
Histologically the wall of alimentary canal of Anoplodesmus tanjoricus is composed of five cellular layers, progressing internally these are, sheath layer, longitudinal muscle layer, circular muscle layer, basement membrane and columnar epithelial layer. Foregut and hindgut are lined internally with cuticular intima, however, mid gut is lined internally with peritrophic membrane. Sheath layer is absent in the foregut region. Oesophageal valve is present between the foregut and mid gut which possibly regulates the passage of food from the foregut into the midgut. Sheath layer is highly developed in the mid gut epithelium. Bundles of muscle fibres are embedded in the sheath layer. These bundles form longitudinal thickenings on the surface of the mid gut well. Circular muscles are poorly developed. The columnar epithelial cells presents distinctive brush border of microvilli. In the posterior region, the mid gut epithelium shows folding and cuticular intima is also seen. Circular muscles are well developed, sheath layer is reduced and longitudinal muscle bundles are seen outside the circular muscle layer. Pylorus marks the junction of mid gut and hindgut. Hindgut is divisible into ileum, colon and rectum. In this region, circular muscles are well developed, longitudinal muscle bundles are distributed unevenly around the circular muscle layer and sheath layer is absent.